Quantification of Transport across the Boundary of the Lower Stratospheric Vortex during Arctic Winter 2002/2003 - Günther, G.; Müller, R.; von Hobe, M.; Stroh, F.; Konopka, P.; Volk, C. M. (EGU, 2008)
Strong perturbations of the Arctic stratosphere during the winter 2002/2003 by planetary waves led to enhanced stretching and folding of the vortex. On two occasions the vortex in the lower stratosphere split into two secondary vortices that re-merged after some days. As a result of these strong disturbances the role of transport in and out of the vortex was stronger than usual. An advection and mixing simulation with the Chemical Lagrangian Model of the Stratosphere (CLaMS) utilising a suite of inert tracers tagging the original position of the air masses has been carried out. The results show a variety of synoptic and small scale features in the vicinity of the vortex boundary, especially long filaments peeling off the vortex edge and being slowly mixed into the mid latitude environment. The vortex folding events, followed by re-merging of different parts of the vortex led to strong filamentation of the vortex interior. During January, February, and March 2003 flights of the Russian high-altitude aircraft Geophysica were performed in order to probe the vortex. filaments and in one case the merging zone between the secondary vortices. Comparisons between CLaMS results and observations obtained from the Geophysica flights show in general good agreement.Several areas affected by both transport and strong mixing could be identified, allowing explanation of many of the structures observed during the flights. Furthermore, the CLaMS simulations allow for a quantification of the air mass exchange between mid latitudes and the vortex interior. The simulation suggests that after the formation of the vortex was completed, its interior remaind relativel undisturbed. Only during the two re-merging events were substantial amounts of extra-vortex air transported into the polar vortex. When in March the vortex starts weakening additional influence from lower latitudes becomes apparent in the model results.